Faktor-Faktor Penyebab Turistifikasi Kawasan Pura Babakan Pada Era Globalisasi - Prawira, Dewa Made Mega; Pujaastawa, Ida Bagus Gde; Tagel Eddy, I Wayan (Humanis, 2023)
The Pura Babakan area is famous for its grandeur of the Pohon Kayu Putih which is a type of Ficus variegata which located in Banjar Bayan, Desa Tua, Tabanan. The purpose of this research is to explain the factors behind the tourisitification of the Pura Babakan area. The research uses critical ethnographic methods with a cultural studies approach. Data collection was carried out using observation, interviews, and literature studies. The results of this study revealed that there were four factors behind the touristification of the Pura Babakan area, namely globalisation factors, market ideology factors, the mythical factor of the success of Bali tourism, and the development of social media.